PENERAPAN METODE AHP UNTUK PENENTUAN SISWA TERBAIK DI SMP YAPINDO II - Dicky Ilhamulya Yahya; Erik Mikael; Yudha Jihad Gilang Ramadhan; Mohammad Badrul (LPPM Universitas Bina Sarana Informatika, 2021)
The desire to be the best student in school is a dream for all school students. In order to become the best students themselves, students must be based on good abilities and knowledge. But sometimes in the selection of the best students there is often an error in determining the existing criteria and several other influencing factors. For example, from the education unit at SMP YAPINDO II, which currently has difficulty determining the best students, human errors and errors in data input often occur. This research was conducted by a team of writers at SMP YAPINDO II using the Analytical Hierarchy Process (AHP) method with a decision support system as a tool to implement the method. The criteria chosen to determine the best students include report cards, absenteeism, and attitude scores. The AHP method was chosen because it can facilitate the preparation of existing criteria, so the AHP method is the right method in making multi-criteria decisions, so that it can produce a relevant decision in determining the best students at YAPINDO II Junior High School.